Pengaruh Pendidikan Kewirausahaan, Kepribadian Wirausaha dan Program Market Day di Sekolah Terhadap Motivasi Berwirausaha Siswa - Letty Meisitha; Pujiati Pujiati; Suroto Suroto (FKIP Universitas Lampung, 2020)
This study aims to determine the effect of entrepreneurship education, entrepreneurial personality, and market day programs in schools on SMK Bhakti Utama Bandar Lampung's entrepreneurial motivation. This research uses a descriptive verification method with an ex post facto approach and survey. The population in this study amounted to 78 students. The samples obtained were 65 students. The results showed an effect of entrepreneurship education, entrepreneurial personality, and market day programs in schools on the entrepreneurial motivation of SMK Bhakti Utama Bandar Lampung students. This is evidenced by the calculation of Fcount Ftable or 27.193 2.76 and a significant value (Sig.) Α = 0.05 or 0.000 0.05. The coefficient of determination (r2) is 0.572 or 57.2%. Entrepreneurial motivation is influenced by entrepreneurial education, entrepreneurial personality, market day programs in schools, and other factors that influence the remaining 42.8%.